Caso para diagnóstico Case for diagnosis - Francine Batista Costa; Rodrigo Pereira Duquia; Paulo Ricardo Martins Souza; Gerson Vettorato; Hiram Larangeira de Almeida Jr (Sociedade Brasileira de Dermatologia, 2009)
O eritema elevatum diutinum é vasculite cutânea rara. Caracteriza-se por pápulas e nódulos eritêmato-acastanhados, que podem coalescer formando placas. A região extensora dos membros é a mais acometida, e lesões antigas apresentam aspecto xantomatoso. O exame histopatológico apresenta infiltrado neutrofílico perivascular com depósito dérmico de fibrina, edema endotelial e leucocitoclasia. Apresenta-se um caso de eritema elevatum diutinum sem doença secundária associada. Erythema elevatum diutinum is a rare presentation of cutaneous vasculitis. Typical lesions are papules, plaques, and nodules that may coalesce and later turn to yellow-brown color. The extensor surface of the extremities is the most involved area and older lesions may present xanthomatous appearance. Light microscopy of acute lesions shows neutrophilic, perivascular infiltrate with dermal fibrin deposits, endothelial expansion, and leukocytoclasis. We present a case of erythema elevatum diutinum without associated disease.